(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the effect of profanity on the kitchen employees of Jollibee in Sm. North Edsa, Quezon City, in terms of work stress, work productivity, job satisfaction, work environment, and work performance. Profanity at work is a problem in some food industries, as it can be used to express emotions, vent, and release, but it can also be seen as disrespectful and rude and cause disciplinary action. From the results of this study, The majority of the respondents are females who are working on food preparation in the morning shift. Most of them are experiencing personal issues with their coworkers and a toxic environment inside their workplace that can cause them to not be productive and not be satisfied with their work because of the profanity that they experience. This study recommends that individuals talk about the problems that can cause unhealthy relationships at work or confront the person who is involved. Hold a meeting if there are bad things happening in the workplace and discuss the situation of employees if they experience bad treatment in the workplace. Be professional and be a good example to employees. Don’t let your temper get to you. Create a policy that prohibits the use of bad language at work. Give the right to punish anyone who disobeys it. Do activities that will help the employees to have a good relationship with each other.